Evaluation of Handwashing Facilities in Basic Schools in Ejura-Sekyeredumase Municipality, Ghana - Richard, Amankwah Kuffour; Paul, Amihere-Ackah; Ebenezer, Acquah (Journal of Sustainability and Environmental Management, 2023)
Hand washing has been recognized as an effective measure against the transmissions of different communicable diseases. This article provided insights into hand washing facilities, students’ knowledge, and patronage of the facilities in basic schools in Ejura-Sekyeredumase Municipality of Ghana motivated by the Covid-19 pandemic. We pointed out the current state of handwashing facilities and knowledge of proper handwashing among basic schools in the second Covid-19 hotspot region.  The study spanned between November 2019 to March 2020. From pre Covid-19 period to the time (month) Ghana recorded its first case of Covid-19. The study was undertaken using well designed structured questionnaire, observation checklist and interviews. It involved randomly sampling 25 public schools and 5 private schools. From each of these 30 schools, 19 students and a teacher were selected randomly and purposively making a total of 600 respondents. Data obtained from the students and staff were compared for their effective relationships using Statistical Package for Social Sciences (SPSS) Version 20. The Pearson Chi-Square test was used to show the effect size and the strength of relationship between variables. The results showed that the handwashing facilities were not enough for students and teachers. Many students rated availability of handwashing materials as good (66. 70%). There was a statistically significant difference (p